Pengembangan teknologi formulasi insektisida nabati untuk pengendalian hama sayuran dalam upaya menghasilkan produk sayuran sehat - . Dadang; Djoko Prijono (Jurnal Ilmu Pertanian Indonesia, 2011)
The use of synthetic insecticide for pest management to protect insect attacking the holticulture product have been done intensivelly and seems not wise which predicted could cause a negative impact to the environmental and human health. Due to that reason then the research prepared to know the pest management technology especially for holticultural product through the use of material or something that come from the agricultural planting material as natural insecticide which could be developed as commercial products that practice and safe to produce healty holticultural product. Three species of fruits and holticultural plant used for the research namely Annona squamosa (Annonaceae/ seed), Piper retrofractum (Piperaceae/fruit) and Tephrosia vogelii (Leguminosae/Leaves) extracted with methanol. Every extract product tested with larva of Cricidolomia pavonana F. (Lepidoptera : Crambidae), that is one of the pest for holticultural product which treated with direction the planting and in the leaves. The extract was tested also to the food barrier of C. Pavonana. The extract of A. Squamosa was contact toxic than abdomen toxic, while on the contrary the extract of P. retrofractum have more impart to the abdomen toxic than contact toxic. The extract of P. Retrofractum and A. Squamosa at the concertation of 0.2 °/o could protect food activities of the larvas that was about 80 °/o. The mixed extract of T. Voge/ii and A. Squamosa more toxic or more effective than the mixed extract of T. Vogelii and P. Retrofractum. In the developing natural insecticide formula, the using of agristic adjuvant was better than tween and miracle especially in formulation establishization. The treatment of P. Retrofractum and T. Vogelii in the field could reduce the development of C. Pavonana which finally those both extract could be used wider as combined with A. Squamosa extract in order to increase the effectiveness.